Strengthening measurement and performance of HIV prevention programmes. Issue 5 (May 2021) - Holmes, Charles B; Kilonzo, Nduku; Zhao, Jinkou; Johnson, Leigh F; Kalua, Thokozani; Hasen, Nina; Morrison, Michelle; Marston, Milly; Smith, Tyler; Benech, Irene; Baggaley, Rachel; Carter, Anna; et al.
Summary: Indicators for the measurement of programmes for the primary prevention of HIV are less aligned than indicators for HIV treatment, which results in a high burden of data collection, often without a clear vision for its use. As new evidence becomes available, the opportunity arises to critically evaluate the way countries and global bodies monitor HIV prevention programmes by incorporating emerging data on the strength of the evidence linking various factors with HIV acquisition, and by working to streamline indicators across stakeholders to reduce burdens on health-care systems. Programmes are also using new approaches, such as targeting specific sexual networks that might require non-traditional approaches to measurement. Technological advances can support these new directions and provide opportunities to use real-time analytics and new data sources to more effectively understand and adapt HIV prevention programmes to reflect population movement, risks, and an evolving epidemic.